Tobacco and alcohol use among drug users receiving methadone maintenance treatment: a cross-sectional study in a rural prefecture of Yunnan Province, Southwest China - Duan, Song (BMJ Open, 2017)
OBJECTIVE: To estimate the prevalence of ever, current and heavy tobacco and alcohol use and their correlates among patients undergoing methadone maintenance treatment (MMT). DESIGN: Cross-sectional study. SETTING: The study was conducted in all of the 5 MMT clinics in Dehong Prefecture, China. PARTICIPANTS: 2121 (81.6%) eligible MMT participants were included in the study population. ANALYSIS: Ordinal logistic regression was used to estimate the ORs and their 95% CIs. RESULTS: The overall prevalence of ever, current and heavy smoking was 98.6%, 97.8% and 66.3%, respectively; while that of ever, current and hazardous alcohol drinking was 86.6%, 58.6% and 16.6%, respectively. Among HIV-infected participants, the proportions of those experiencing harmful effects of tobacco and alcohol on AIDS were 53.6% and 72.5%, respectively, and 16.9% and 49.3% had ever tried to quit after diagnosis with HIV. After adjusting for potential confounders, heavier smokers and more hazardous drinkers were more likely to be men, older and less educated. Ethnic minorities were less likely to heavily smoke, but more likely to engage in hazardous drinking. In addition, hazardous drinking was negatively associated with longer years of MMT and HIV infection. Moreover, heavier smoking (OR(≥2)=2.08, 95% CI 1.16 to 3.73) and more hazardous drinking (OR(≥2)=2.46, 95% CI 1.53 to 3.97) were positively associated with having multiple sexual partners, and both were positively associated with each other. CONCLUSIONS: The prevalence of tobacco and alcohol consumption was extraordinarily high among MMT participants in China, suggesting the urgent need of enhancing MMT patients' awareness of the harmful effects of tobacco and alcohol consumption and implementing comprehensive education and effective intervention programmes.